KRISIS EKONOMI DALAM PERSPEKTIF ISLAM REFLEKSI KRISIS TAHUN RAMADAH PADA ERA UMAR BIN KHATHAB - fasya fasya (IAIN Langsa, 2016)
Economic crisis is an event where economic sector is being devastated due to numerous factors. In Islamic goverment history, there was once a severe economic crisis known as Ramadah year crisis which happened during Umar bin Khathab goverment. Beside analysing the causes and effects of the crisis, Umar bin Khathab also offered some concrete solutions for overcoming the crisis in the short and long-term period. Beside the solutions practiced by Umar bin Khathab, there are many other precise and relevant solutions to be implemented in today’s modern life.